PRODUCTION OF GREEN DIESEL BASED ON PALM FATTY ACID DISTILLATE USING CATALYTIC HYDROGENATION METHOD - Fithra Malvarinda; Adi Syakdani; Muhammad Taufik (OISAA, 2022)
Green diesel is an alkane compound that is equivalent to petroleum based diesel oil. One of the ingredients that can be converted into green diesel is Palm Fatty Acid Distillate (PFAD). PFAD is a by-product of the refinery process in the production of cooking oil from Crude Palm Oil (CPO) which has not been widely used. Green diesel is produced using a catalytic hydrogenation process at a temperature of 300oC with a hydrogen pressure of 25 psia for 1.0 hour. 300 ml of PFAD is reacted with gas (hydrogen) H2 using NiMo / Al2O3 catalyst to accelerate the reaction. The variable that is used in this study is the number of catalysts of 0 gr; 0.1114 gr; 0.1507 gr; 0.2009 gr; 0.2541 gr; and 0.3075 gr. The use of a catalyst of 0.2009 grams per 300 ml of sample is the optimum condition in this study and yields a yield percentage of 36.5331%. The physical properties of green diesel obtained from this study include density at 40oC (751.5056 – 816.9221 kg/m3), kinematic viscosity at 40oC (3.6107 – 4.6831 mm2/s), moisture content (11.593 – 17.717 ppm), flash point (65.4 – 91.9oC), and heating value (43.2274 – 44.8834 MJ / kg).